2000
DOI: 10.1149/1.1393490
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical-Thermal Model of Lithium Polymer Batteries

Abstract: A mathematical model has been developed to study heat transfer and thermal management of lithium polymer batteries. Temperature dependent parameters including the diffusion coefficient of lithium ions, ionic conductivity of lithium ions, transference number of lithium ions, etc., have been added to a previously developed electrochemical model to more completely characterize the thermal behavior of the lithium polymer system. In addition, experimental studies of the discharge behavior and heat generation rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(119 citation statements)
references
References 17 publications
1
118
0
Order By: Relevance
“…However, because no investigations actually report the heat rate on a volume basis, cross-study comparison requires significant manipulation of the reported data. This includes estimating the heat rate from the total cell volume, [54][55][56][59][60][61][62][63][64][65][66][67][68]70 from the thickness of the unit cell 49 or the entire battery, 69 or from standard densities of full cells. 57,58 Unfortunately, these assumptions can greatly influence the estimated volumetric heat generation rate.…”
Section: R8mentioning
confidence: 99%
“…However, because no investigations actually report the heat rate on a volume basis, cross-study comparison requires significant manipulation of the reported data. This includes estimating the heat rate from the total cell volume, [54][55][56][59][60][61][62][63][64][65][66][67][68]70 from the thickness of the unit cell 49 or the entire battery, 69 or from standard densities of full cells. 57,58 Unfortunately, these assumptions can greatly influence the estimated volumetric heat generation rate.…”
Section: R8mentioning
confidence: 99%
“…The blue line shows the actual capacity values calculated by equation (6). The measured capacity values are shown by the red dots, which were simulated as the actual capacity values at cycle k plus independent zero-mean Gaussian noise terms and expressed as measurement model equation (13). The green line represents the prediction points, which were estimated by particle filtering equations (10) to (12).…”
Section: State Transition Modelmentioning
confidence: 99%
“…Researchers worldwide have developed a wide variety of battery models for different purposes. Almost all the existing battery models can be classified into the following two types: (1) parametric models, e.g., electrochemical models [1,2] and electrical models [3][4][5][6]; and (2) nonparametric models, e.g., artificial neural network (ANN) models [7][8][9] and abstract mathematical models [10]. Parametric battery models have been developed in terms of the equivalent electric-circuit parameters (for electrical models) or electrochemical parameters (for electrochemical models).…”
Section: Introductionmentioning
confidence: 99%